Dutiful Love Empowering Individuals and Families Affected by Mental Illness. - HINSON-HASTY, ELIZABETH L. (Book collections on Project MUSE., 2021)
Dutiful Love explores the distinctive relationship between self-sacrificial love and caregiving when that duty to care extends over the course of an entire lifetime because of social limitations placed upon people with severe mental illness. The author draws upon her own experiences as the sibling of someone with mental illness. The book includes discussion questions, making it an ideal resource for individual reflection, church study groups, and college, seminary, and university classrooms.